Las abuelas de Liliana - Torres, Leyla (New York : Scholastic, 1998)
Because one of her grandmothers lives down the street and the other in a far away country, Liliana experiences two very different ways of life when she visits them.
"MIRASOL/libros juveniles."
Accelerated Reader
Keywords: Grandmothers -- Juvenile fiction; Abuelas -- Novela juvenil